Mixing ratio optimization for functional complex extracts of Rhodiola crenulata, Panax quinquefolius, and Astragalus membranaceus using mixture design and verification of immune functional efficacy in animal models. (January 2018) - Hong, Hee-Do; Kim, Jong-Chan; Lim, Tae-Gyu; Song, Young-Ran; Cho, Chang-Won; Jang, Mi
Highlights: We aimed to identify the optimum mixing ratio for various ingredients. The extract yield and amounts of NO and IL-6 were set to maximum for modeling. At the optimum values, and 35.3% yield, 14.7% NO, and 6.6% IL-6 were obtained. The combined extract increased the spleen index and T- and B-cell proliferation. These results provide a basis for the development of functional extracts and drinks. Abstract: We aimed to identify the optimum mixing ratio for various ingredients to obtain complex extracts with high extract yields and immune-enhancing activity in animals. The extract yield and amounts of nitric oxide (NO) and interleukin (IL)-6 were set to maximum for modeling predictions. The predicted optimum values for the mixing ratio were 49.5% for Rhodiola crenulata, 26.1% for Astragalus membranaceus, and 24.4% for Panax quinquefolius, and the predicted response values were 31.5% yield, 13.4% NO production, and 6.1% IL-6 production; actual values were 35.3% yield, 14.7% NO, and 6.6% IL-6. The optimum mixing ratio extract (OMRE) was used for the animal experiments. Treating mice with OMRE at 200 mg/kg produced significant increases in spleen indexes and T-cell/B-cell proliferation. OMRE treatment increased IL-10 and IL-6 production in concanavalin A- and lipopolysaccharide-induced T- and B- lymphocytes, respectively. These results provide a basis for the development of functional extracts and drinks.